Kain Telepuk: The Selangor Malay royal textile / Mohd Jamil Muhamad Amin and Arbai’yah Ab. Aziz - Muhamad Amin, Mohd Jamil; Ab. Aziz, Arbai’yah (2019)
‘Kain Telepuk’ is the most glorious Malay textile. In the state of Selangor, the Telepuk textile is a rich fabric usually worn by the royalty and nobility members since 300 years ago. The Telepuk textile is widely used during the reign of the High Royal Highness Sultan Sir Hishamuddin Alam Shah Al-haj (1938–1960) and worn by his consort the Royal Highness Tengku Ampuan Jemaah. Telepuk textile is not popular and the choice of ideas to the local fashion designers. Today younger generations, especially Malays are not familiar and unacknowledged about the Telepuk textile as the great Malay traditional textile art form. This research is to identify the floral motif of the Telepuk textile and leaded to a systematic inquiry in documenting the aesthetic values of the Malay treasure of the Malay Selangor heritage textile. This study also is to document and compile the aesthetic and philosophical values of treasure of the Telepuk textile as the Selangor Malay traditional royal court fabric.